ПЕРВЫЕ ДАННЫЕ ПО КАРПИНСКИОЗАВРИДАМ (SEYMOURIAMORPHA, PARAREPTILIA) ИШЕЕВСКОГО ФАУНИСТИЧЕСКОГО КОМПЛЕКСА - Буланов B.В. (My University, 2005)
A revision of terrestrial vertebrates corroborates The Early Tatarian age of the Vozdvizhenka locality (Orenburg Region). Most vertebrates from this locality belong to the family Karpinskiosauridae, which has not previously been recorded in the Isheevo Faunal Assemblage of eastern Europe. Isolated dermal bones of the skull of Karpinskiosaitms from the Vozdvizhenka locality are described and compared with other members of the family.